COMPARISON OF RAPID UREASE TEST WITH IMMUNOHISTOCHEMICAL EXAMINATION OF GASTRIC MUCOSA SPECIMEN IN THE DIAGNOSTICS OF HELICOBACTER PYLORI INFECTION AMONG OUTPATIENTS - Anna Bryczkowska; Tomasz Arłukowicz; Leszek Paweł Gromadziński (Polish Journal of Natural Sciences, 2025)
Helicobacter pylori infection affects half of the human population. It is the most common infection in the world. Its presence is associated with numerous complications, including gastric cancer. More than 30 years ago, this bacterium was included by the World Health Organisation in the list of class 1 carcinogens, precisely because of its link to gastric cancer (Cho et al. 2021, Lee et al. 2024, Tobi et al. 2023). Its prevalence varies depending on geographical location, and even within a single country, different incidence rates have been reported (Cho et al. 2021, Codolo et al. 2022). Infection most often occurs around the age of 10 and is usually asymptomatic. Therefore, it slowly leads to numerous complications. Relatively few patients experience symptoms associated with this condition and seek medical attention. The diagnostic pathway includes non-invasive and invasive tests, depending on the patient’s age and the presence of worrying symptoms.